1978
DOI: 10.1073/pnas.75.3.1562
|View full text |Cite
|
Sign up to set email alerts
|

Diet, genetics, and mental retardation interaction between phenylketonuric heterozygous mother and fetus to produce nonspecific diminution of IQ: Evidence in support of the justification hypothesis

Abstract: ,Diet, genetics, and mental retardation interaction between phenylketonuric heterozygous mother and fetus to produce nonspecific diminution of IQ: Evidence in support of the justification hypothesis (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
1

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 14 publications
2
17
1
Order By: Relevance
“…Ford and Berman (9) showed that in siblings with PKU, the heterozygotes (identified by phenylalaninetyrosine conversion tests) had significantly lower IQs than their siblings who had normal results on conversion tests. Similar results were reported subsequently by another group (10). This finding could not be explained by phenylalanine toxicity.…”
supporting
confidence: 81%
“…Ford and Berman (9) showed that in siblings with PKU, the heterozygotes (identified by phenylalaninetyrosine conversion tests) had significantly lower IQs than their siblings who had normal results on conversion tests. Similar results were reported subsequently by another group (10). This finding could not be explained by phenylalanine toxicity.…”
supporting
confidence: 81%
“…During all four pregnancies plasma phenylalanine could be kept below the 'critical' level of 600/zmolL -1 (Levy and Waisbren, 1983), most values being lower than 500 tzmol t -1. In order to avoid tyrosine deficiency (Brouwer et al, 1977;Bessman et al, 1978), increasing amounts of this amino acid were given. In spite of supplementation fasting tyrosine concentrations were often rather low.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these methodologies centered on the assay of blood phenylalanine (P) and/or tyrosine (T) with or without phenylalanine dose loading. In the present report, we compared our methods on a larger sample size to two other published discriminant analysis methods and also to the P2/T dose loading method of Bessman et al (1978). Using our discriminant function derived from fasting blood P and T levels, we reported that 10% of our subjects could not be classified without retesting (Tenenholz et al 1983).…”
mentioning
confidence: 92%